2015
DOI: 10.1089/ast.2015.1306
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Building Blocks of Life on Europa and Other Icy Moons

Abstract: The outer Solar System may provide a potential habitat for extraterrestrial life. Remote sensing data from the Galileo spacecraft suggest that the jovian icy moons-Europa, Ganymede, and possibly Callisto-may harbor liquid water oceans underneath their icy crusts. Although compositional information required for the discussion of habitability is limited because of significantly restricted observation data, organic molecules are ubiquitous in the Universe. Recently, in situ spacecraft measurements and experiments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 89 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…Experiments investigating the tolerance of Earth organisms to extreme conditions have been carried out with an eye toward an application to the environments of the early Earth (Cnossen et al, 2007;Westall et al, 2011;Grosch & Hazen, 2015), solar system planets like Mars (Navarro-González et al, 2003;Cockell & Raven, 2004;Diaz & Schulze-Makuch, 2006;de la Vega et al, 2007;Dartnell et al, 2010), the moons of the outer solar system such as Jupiter's moon Europa (Chyba, 2000;Chyba & Phillips, 2002;Deming, 2002;Marion et al, 2003;Bulat et al, 2004Bulat et al, , 2011Kimura & Kitadai, 2015;Noell et al, 2015), and interplanetary space (Paulino-Lima et al, 2010). However, given the varied factors that may influence the climate and surface environment of M-dwarf planets, much of what has been learned about the mechanisms employed by extremophilic life on Earth to not only survive but thrive has implications for the likelihood of life to grow and evolve on planets in close-in orbits around these small, cool stars.…”
Section: Where Life Can Survive On M-dwarf Planetsmentioning
confidence: 99%
“…Experiments investigating the tolerance of Earth organisms to extreme conditions have been carried out with an eye toward an application to the environments of the early Earth (Cnossen et al, 2007;Westall et al, 2011;Grosch & Hazen, 2015), solar system planets like Mars (Navarro-González et al, 2003;Cockell & Raven, 2004;Diaz & Schulze-Makuch, 2006;de la Vega et al, 2007;Dartnell et al, 2010), the moons of the outer solar system such as Jupiter's moon Europa (Chyba, 2000;Chyba & Phillips, 2002;Deming, 2002;Marion et al, 2003;Bulat et al, 2004Bulat et al, , 2011Kimura & Kitadai, 2015;Noell et al, 2015), and interplanetary space (Paulino-Lima et al, 2010). However, given the varied factors that may influence the climate and surface environment of M-dwarf planets, much of what has been learned about the mechanisms employed by extremophilic life on Earth to not only survive but thrive has implications for the likelihood of life to grow and evolve on planets in close-in orbits around these small, cool stars.…”
Section: Where Life Can Survive On M-dwarf Planetsmentioning
confidence: 99%
“…McCord and Castillo-Rogez, 2018; McCord and Zambon, 2019; Neveu and Desch, 2015;Villarreal et al, 2017;Vu et al, 2017;Zolotov, 2009 Ion sputtering of the surface; potential water plumes ; O2; trace amounts of sodium and potassium Cassidy et al, 2013;Chyba and Phillips, 2001;Hand and Carlson, 2015;Jones et al, 2018;Kattenhorn and Prockter, 2014;Kimura and Kitadai, 2015;Marion et al, 2005;Martin and McMinn, 2018;McGrath et al, 2009;Muñoz-Iglesias et al, 2013;Noell et al, 2015;Pavlov et al, 2018;Soderlund et al, 2014;Spencer et al, 1999;Teolis et al, 2017;Travis et al, 2012;Vance et al, 2016;Zolotov and Kargel, 2009 Surface (icy shell) -187 --141 nr 0. Potential for wide range q 0.1 -30 r <3.5 Likely contains Mg 2+ , SO4 2-, Na + , Cl -; oxidants and simple organics a -Thermosphere can be as cold as -173ºC (Bertaux et al, 2007); the upper-to-middle cloud layers are between -40-60ºC (Cockell, 1999) b -Acid concentration in upper cloud layer is 81%, in lower layers up to 98% (Cockell, 1999) c -Up to 11 MPa in a deep depression (Basilevsky and Head, 2003) d -Summer air temperatures on Mars near the equator can reach a maximum of 35ºC (Longstaff, 2014) e -Measured by the Phoenix Mars Lander Wet Chemistry Laboratory at the northern plains of the Vastitas Borealis (Hecht et al, 2009) f -Liquid water may have had water activity > 0.95 (Fairén et al, 2009) g -Calculated temperature at a depth of 1-30 km (Sinha2017, Jones2011); at a depth ~310 km, the calculated temperature is <427ºC (Jones 2011); the Martian core has temperature 1527ºC…”
Section: Future Directions and Outlookmentioning
confidence: 99%
“…Kimura and Kitadai ( 2015 ) performed a theoretical analysis of the free energy available to drive peptide condensation reactions at the very low surface temperatures of Europa. They concluded that at temperatures below 118 K, the Gibbs energy becomes negative, which means, for instance, that diglycine can be synthesized from glycine on Europa and other icy moons.…”
Section: Polymer Synthesismentioning
confidence: 99%